FRONT-END INTERFACE DESIGN AND IMPLEMENTATION OF A WEB-BASED INVENTORY INFORMATION SYSTEM FOR TRAINING INSTITUTES IN JAKARTA (POLITEKNIK LP3I JAKARTA, 2026)
Background: Managing inventory data in non-formal educational institutions with multiple branches frequently encounters synchronization barriers when conducted manually through conventional recording methods. Objective: This study aims to design and implement an integrated web-based inventory information system front-end interface to enhance operational efficiency, data integrity, and asset monitoring transparency across various Training Centers (TCs). Methodology: Adopting a linear sequential (Waterfall) software development model, this research encompasses interface requirements analysis, visual architecture design (wireframes and prototypes), code implementation, and rigorous system testing. Data collection was executed through field observations, in-depth interviews, and a comprehensive literature review. Findings: This study delivers a responsive, structured, and user-friendly inventory interface developed using core web technologies: HTML5, CSS3, JavaScript, and the Bootstrap framework. Interface testing via the black-box methodology demonstrates that the visual system dynamically adapts across diverse device screen resolutions and modern web browsers. Conclusion: The developed system effectively minimizes the risks associated with data redundancy while optimizing centralized asset condition tracking within training institutes in Jakarta.